Human megakaryocytes possess intrinsic antiviral immunity through regulated induction of IFITM3 - Campbell, Robert A.; Schwertz, Hansjorg; Hottz, Eugenio D.; Rowley, Jesse W.; Manne, Bhanu Kanth; Washington, A. Valance; Hunter-Mellado, Robert; Tolley, Neal D.; Christensen, Miles; Eustes, Alicia S.; Montenont, Emilie; Bhatlekar, Seema; et al. (Blood, 2019)
Evolving evidence indicates that platelets and megakaryocytes (MKs) have unexpected activities in inflammation and infection; whether viral infections upregulate biologically active, antiviral immune genes in platelets and MKs is unknown, however. We examined antiviral immune genes in these cells in dengue and influenza infections, viruses that are global public health threats. Using complementary biochemical, pharmacological, and genetic approaches, we examined the regulation and function of interferon-induced transmembrane protein 3 (IFITM3), an antiviral immune effector gene not previously studied in human platelets and MKs. IFITM3 was markedly upregulated in platelets isolated from patients during clinical influenza and dengue virus (DENV) infections. Lower IFITM3 expression in platelets correlated with increased illness severity and mortality in patients. Administering a live, attenuated DENV vaccine to healthy subjects significantly increased platelet IFITM3 expression. Infecting human MKs with DENV selectively increased type I interferons and IFITM3. Overexpression of IFITM3 in MKs was sufficient to prevent DENV infection. In naturally occurring, genetic loss-of-function studies, MKs from healthy subjects harboring a homozygous mutation in IFITM3 (rs12252-C, a common single-nucleotide polymorphism in areas of the world where DENV is endemic) were significantly more susceptible to DENV infection. DENV-induced MK secretion of interferons prevented infection of bystander MKs and hematopoietic stem cells. Thus, viral infections upregulate IFITM3 in human platelets and MKs, and IFITM3 expression is associated with adverse clinical outcomes. These observations establish, for the first time, that human MKs possess antiviral functions, preventing DENV infection of MKs and hematopoietic stem cells after local immune signaling. •Viral infections upregulate IFITM3 in human platelets and MKs, triggering rapid antiviral immune responses.•MKs are effective immune cells that prevent virus infection in naive MKs but also limit infection in bystander hematopoietic stem cells. [Display omitted]